2013
DOI: 10.2106/jbjs.l.00481
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Chronic Exertional Compartment Syndrome of the Leg

Abstract: Chronic exertional compartment syndrome is a substantial contributor to lower-extremity disability in the military population. Nearly half of all service members undergoing fasciotomy reported persistent symptoms, and one in five individuals had unsuccessful surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…The percentage of patients requiring revision fasciotomy after release of all lower leg compartments has been reported in the literature to be as high as 20%. 21 , 24 This shows that requiring revision surgery is a relatively common outcome after release. By comparison, in this study, only 1 leg required revision anterolateral surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of patients requiring revision fasciotomy after release of all lower leg compartments has been reported in the literature to be as high as 20%. 21 , 24 This shows that requiring revision surgery is a relatively common outcome after release. By comparison, in this study, only 1 leg required revision anterolateral surgery.…”
Section: Discussionmentioning
confidence: 99%
“…29 , 33 While the majority of patients do well after surgery, approximately 3% to 17% experience less than favorable outcomes such as pain, decreased sensation or hypersensitivity to touch at the incision site, paresthesia, infection, and hemorrhage. 7 , 13 , 19 , 30 , 37 Additionally, even individuals who do well initially may have a risk of symptom recurrence, which is reported to be as high as 50% over 5 years. These less favorable operative outcomes and the morbidity burden that postoperative rehabilitation has on military readiness gives great relevance to discovering alternative strategies for effective nonoperative CECS management.…”
mentioning
confidence: 99%
“…One study looking at a population of military men under extreme physical demand showed persistence of symptoms to some degree in up to 50% of patients. This study, also found that surgical revision may be needed in up to 6% of patients [ 15 ]. This study highlighted the high physical demand and increased body weight due to carrying equipment, yet patients experienced an 80% successful return to activity.…”
Section: Discussionmentioning
confidence: 89%
“…Surgical results are better in CECS cases involving the lateral and anterior compartments when compared to posterior compartments [ 12 , 13 ]. Fasciotomy is effective in the treatment of CECS with a success rate of 80% or greater [ 3 , 8 , 14 , 15 ]. One study looking at a population of military men under extreme physical demand showed persistence of symptoms to some degree in up to 50% of patients.…”
Section: Discussionmentioning
confidence: 99%